Detection of rabies viral neutralizing antibodies in the Puerto Rican Brachyphylla cavernarum - Andrew Hirsbrunner (Taylor & Francis Group, 2020)
The purpose of this study was to determine if Puerto Rican bats had previous exposure to rabies virus based on viral neutralizing antibodies. Our results demonstrate that 6.5% of the bats in this study had some exposure to rabies virus. The route of exposure is unknown but may have occurred following interaction with a rabid terrestrial animal or an unidentified bat rabies virus.